Ultrasound 2020
DOI: 10.1183/13993003.congress-2020.2785
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of contrast-enhanced thoracic ultrasound (CETUS) compared to standard reference tests: a systematic review

Abstract: Contrast-enhanced ultrasound is utilized in an increasing array of medical fields, including thoracic medicine. However, the technique is still relatively new and only sporadically mentioned in current guidelines and recommendations. The aim of this systematic review is to provide a literature overview and critically appraise the current clinical applications of contrast-enhanced thoracic ultrasound (CETUS). Materials and Methods:A systematic literature search using major electronic databases and in accordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…As for CEUS, the perfusion mode, degree of enhancement, homogeneity, microvascular characteristics, and especially AT are recommended indicators ( 8 19 ). However, studies that proposed the above indicators also has limitations, including small sample size, inconsistent conclusions from different researchers, strong subjectivity, and no multi factor analysis ( 9 ). In this large-scale and multiparameter study, we constructed a new US prediction model for the differential diagnosis of benign and malignant SPLs and obtained good discrimination and calibration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for CEUS, the perfusion mode, degree of enhancement, homogeneity, microvascular characteristics, and especially AT are recommended indicators ( 8 19 ). However, studies that proposed the above indicators also has limitations, including small sample size, inconsistent conclusions from different researchers, strong subjectivity, and no multi factor analysis ( 9 ). In this large-scale and multiparameter study, we constructed a new US prediction model for the differential diagnosis of benign and malignant SPLs and obtained good discrimination and calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative CEUS parameters were measured and calculated according to the time-intensity curve (TIC). We used the TIC analysis software in LOGIQ E9 to select the earliest enhancing areas of air-filled lung tissues, the thoracic wall and the lesion as the regions of interest (ROIs) to plot TICs and obtained the following parameters: (a) AT of lung, (b) AT of thoracic wall, (c) AT of lesion, (d) lesion-lung AT difference, (e) ratio of AT difference, (f) basic intensity (BI), (g) peak intensity (PI), (h) time to peak (TTP), (i) WIR, (j) WOR ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of the current clinical application of contrast-enhanced thoracic ultrasound revealed that its use to guide transthoracic biopsies could increase diagnostic accuracy by 14.6% on average [ 53 ]. However, the use of contrast-enhanced ultrasound to distinguish between benign or malignant lesions is not yet well supported by evidence, as overall the studies were heterogeneous, small and with high risk of bias.…”
Section: Group 1403: Ultrasoundmentioning
confidence: 99%